Interprofessional communication and patient safety in the neonatal intensive care unit - Acosta Alves, Vanessa (2024)
Introduction: Respectful communication includes social, verbal, and non-verbal interaction, including mutual understanding and respecting values, beliefs, and cultural preferences to promote equity in health care. Failures  in the communication process are considered one of the main factors behind the occurrence of adverse events and, consequently, a decrease in the quality of care. Objective: To understand how the interprofessional communication process is developed to ensure patient safety in the Neonatal Intensive Care Unit. Method: Convergent care research carried out from July to August 2019 with 17 professionals from the health team of the Neonatal Intensive Care Unit of a University Hospital in southern Brazil. Results: Two categories were elaborated to present the information collected: Verbal and non-verbal communication; Facilitating and hindering factors in communication. From the theoretical-practical convergence, it was possible to develop a Standard Operating Procedure Protocol for Effective Communication for its practical implementation. Conclusion: Verbal communication during the shift change was perceived as the main tool, contributing to patient care and safety, being the connection between professionals an important factor to improve it. This connection, together with ongoing training, favors effective communication.